Concomitant overexpression of triple antioxidant enzymes selectively increases circulating endothelial progenitor cells in mice with limb ischaemia. Issue 6 (11th April 2019) - Liu, Lingjuan; Cui, Yuqi; Li, Xin; Que, Xingyi; Xiao, Yuan; Yang, Chunlin; Zhang, Jia; Xie, Xiaoyun; Cowan, Peter J.; Tian, Jie; Hao, Hong; Liu, Zhenguo
Abstract: Endothelial progenitor cells (EPCs) are a group of heterogeneous cells in bone marrow (BM) and blood. Ischaemia increases reactive oxygen species (ROS) production that regulates EPC number and function. The present study was conducted to determine if ischaemia‐induced ROS differentially regulated individual EPC subpopulations using a mouse model concomitantly overexpressing superoxide dismutase (SOD)1, SOD3 and glutathione peroxidase. Limb ischaemia was induced by femoral artery ligation in male transgenic mice with their wild‐type littermate as control. BM and blood cells were collected for EPCs analysis and mononuclear cell intracellular ROS production, apoptosis and proliferation at baseline, day 3 and day 21 after ischaemia. Cells positive for c‐Kit + /CD31 + or Sca‐1 + /Flk‐1 + or CD34 + /CD133 + or CD34 + /Flk‐1 + were identified as EPCs. ischaemia significantly increased ROS production and cell apoptosis and decreased proliferation of circulating and BM mononuclear cells and increased BM and circulating EPCs levels. Overexpression of triple antioxidant enzymes effectively prevented ischaemia‐induced ROS production with significantly decreased cell apoptosis and preserved proliferation and significantly increased circulating EPCs level without significant changes in BM EPC populations, associated with enhanced recovery of blood flow and function of the ischemic limb. These data suggested that ischaemia‐induced ROS was differentially involved in the regulation of circulating EPC population.